2005
DOI: 10.1111/j.1525-1497.2005.0242.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial risk factors for adverse outcomes in patients with nonvalvular atrial fibrillation receiving warfarin

Abstract: Patients with nonvalvular atrial fibrillation treated with warfarin who have psychosocial risk factors for nonadherence have an increased risk of adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 37 publications
(53 reference statements)
0
39
0
6
Order By: Relevance
“…[19][20][21][22] In particular, warfarin is underutilized in patients with atrial fibrillation with co-morbid substance abuse, 23 but evidence to support this decision has been sparse. 24 , 25 A recent systematic review found a statistically significant increase in hemorrhages in alcohol abusers in less than half of the studies and reported overall strength of the evidence as low. 25 Poorer anticoagulation control in substance-abusing patients is concerning, since improved control is associated with fewer adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22] In particular, warfarin is underutilized in patients with atrial fibrillation with co-morbid substance abuse, 23 but evidence to support this decision has been sparse. 24 , 25 A recent systematic review found a statistically significant increase in hemorrhages in alcohol abusers in less than half of the studies and reported overall strength of the evidence as low. 25 Poorer anticoagulation control in substance-abusing patients is concerning, since improved control is associated with fewer adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…24 , 25 A recent systematic review found a statistically significant increase in hemorrhages in alcohol abusers in less than half of the studies and reported overall strength of the evidence as low. 25 Poorer anticoagulation control in substance-abusing patients is concerning, since improved control is associated with fewer adverse events. [26][27][28][29][30] The reasons for poorer anticoagulation control among substance abusers are not fully understood, but likely involve pharmacology as well as compliance.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15] Among patients with atrial fibrillation, those with MHCs are known to be less likely to be started on warfarin therapy, 16 and are more likely to have poorly controlled therapy 17 and to experience adverse events such as hemorrhage and stroke. 18 However, important questions regarding MHC and warfarin therapy remain unanswered. We do not know which MHCs are most strongly associated with low TTR and adverse events, and whether MHC-specific risk factors, such as a history of psychiatric hospitalization or the Global Assessment of Functioning (GAF) score, can help to identify an especially vulnerable subgroup of patients.…”
Section: Introductionmentioning
confidence: 99%
“…При этом характеристики психо-патологических расстройств ограничиваются перечислени-ем отдельных симптомов: тревога, соматизация и др. [7,[12][13][14][15][16] и оцениваются в пределах психологических (вну-тренняя картина болезни) или социальных (качество жиз-ни) феноменов [17][18][19][20][21][22].…”
unclassified
“…В других работах [10,16,25] Психосоматические корреляции при фибрилляции предсердий мии, сопровождающейся депрессией, сводится к фиксации длительности и частоты пароксизмов ФП [3,6,[26][27][28]. В то же время вне поля зрения исследователей остают-ся такие психосоматические аспекты ФП, как связь психо-патологических расстройств с патохарактерологическими особенностями пациентов, психогенными факторами, про-воцирующими пароксизмы, а также со стереотипами тече-ния соматической патологии (форма, длительность, тя-жесть, наличие осложнений ФП).…”
unclassified